Enhanced electrical and thermal conductivities of 3D-SiC(rGO, Gx) PDCs based on polycarbosilane-vinyltriethoxysilane-graphene oxide (PCS-VTES-GO) precursor containing graphene fillers. Issue 1 (January 2020) - Han, Yuchen; Zhong, Lei; Zheng, Yinong; Zhou, Rui; Liao, Liang; Chen, Guolong; Huang, Wenyan; Lin, Shuyu; Zhong, Yuejin; Li, Junbin; Zheng, Wei; Yao, Rongqian
Abstract: Lightweight 3D-SiC(rGO, G x ) PDCs were fabricated from polycarbosilane-vinyltriethoxysilane-graphene oxide (PCS-VTES-GO) precursor added by different amounts of graphene fillers via direct cold molding and pyrolysis at 1400 °C in an easy manner. Results reveal that SiC(rGO, G x ) PDCs consist of β-SiC nanocrystals homogeneously embedded within amorphous SiO x C y /Cfree, and graphene is well compatible with SiO x C y /Cfree for void-free bonded interface, efficiently delaying decomposition of SiO x C y phase into β-SiC. The nanocomposite structure provides an ingenious strategy for constructing complexes with good integrity, high ceramic yield, excellent thermal stability, high electrical and thermal conductivities. This improvement is primarily attributed to the presence of graphene with considerably increasing electric-charge carriers and wider phonon-channel. Such 3D-SiC(rGO, G 20% ) PDCs possess satisfying hardness (12.02 GPa), high electrical conductivity (23.82 S cm −1 ) and thermal conductivity (7.47 W m −1  K −1 ), which make them attractive candidates for microelectromechanical systems (MEMS) devices, energy storage/conversion systems and high precision components, etc.